The challenges of local authorities: A case study in Malaysia - Ngah, Kamarudin (Canadian Academy of Oriental and Occidental Culture (CAOOC), 2011)
Rapid development in local authorities nowadays faced with several challenges in demands.Over the years, issues and problems due to poor management, malpractice, and poor finance makes local authorities in dilemmas.The ability to overcome current issues and the readiness to face future challenges are estimated differently due to size and boundary by itself.Local authorities whom are equipped with strong finance, visionary leadership, systematic strategic and action planning, and public support will definitely be more prepared to face those challenges. In other hand, weaker local authorities in financial and effective administration maybe faced problems in its area. Therefore, the objective of this study is to examine in what level of issues and challenges facing by the council in served to the public and what the an approach applied to this study.There are several main findings by using a set of questionnaire on the issues and challenges of local authorities in Malaysia, by referring to Seberang Perai Municipality Council as case study and some information in questionnaires hand over to Ministry of Housing and Local Government (MHLG).Thus, a few recommendations were proposed to its council in designing better approach in servicing public.In future research, the local government should be firmed in addressing the issues and challenges by having good instrument to be measured in their core business.